ANALISIS KESALAHAN BERBAHASA PADA SURAT PPKM DAN PENANGANAN COVID-19 KABUPATEN SUKOHARJO - Maratus Sholikhah; Erva Neilan Navisa; Natarina Novia Angraini (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This study examines language errors in the circular letter for micro-based PPKM extension and optimizes the Covid-19 handling post at the village/sub-district level in Sukoharjo district . The data collection process was carried out by using descriptive analytical methods. The purpose of this study is to describe the forms of language errors in writing circular letters. The result of this analysis can be concluded that there were language errors in writing of the circular letter. In the circular, there are 4 errors, namely 1) syntax errors, 2) semantic errors, 3) diction errors, and 4) spelling errors. Based on the data above, it can be concluded that the tendency for language errors is in the spelling field. Language errors in this research are predominantly language errors at the level of spelling of the writing in this circular.